Roof efficiency assessment for indoor thermal environment in contemporary houses in Najaf City, Iraq - Saleh, Al-Mohsen Mustafa Abdulmunem (2022)
Summer heat can be so severe in Iraq and the ambient temperature could reach higher than 50 °C. Most of the outside surfaces, generally and roofs, specifically are affected by solar radiation beams, which would increase the usage of cooling devices and power consumption in houses. These increases have caused severe electricity shortage during the summer, in addition to the general electricity issues in Iraq. Thus, this study aimed to assess the heat flux through traditional roofs in Iraqi dwellings. The efficiency of these types of roofs in decreasing the amount of heat flux flowing through them was assessed as a second objective. This study has also examined the impact of the double-skin roof strategy (through retrofitting these roofs with a K-span roof cover) on the reduction of the total heat flux and on improving the efficiency of the whole roof as a final objective. The methodology of this study included running simulations using the Comsol Multiphysics software. Simulations were conducted for 72 hours in the summer on the 27th, 28th, and 29th of July, and results were taken within 24-hour intervals for the following parameters: exterior roof surface temperature (Tes); interior roof surface temperature (Tis); indoor room temperature (Tr); total heat flux (Q-value); and roof heat transfer coefficient (U-value). The efficiency results of roof types (RF) before being retrofitted with K-span roof cover showed that the RF3B roof was the only efficient roof with U-value that was better than the Middle East standards by 32.6%. RF3 and RF4 multi-layered roof types showed lower efficiency than the standards by 46.4% and 278%, while RF5 and RF4B single layer roofs were 733% and 603% lower than the standards, respectively. The results of retrofitting the roofs with K-span roof cover demonstrated that the average efficiency of the parameters of Tes, Tis, Tr, Q-value, and U-value that impacted the efficiency of the selected roofs were improved by 54.2% in RF3 (Room 3), 56.9% in RF3B (Room 3B), and 55.1% in RF4 (Room 4). Meanwhile, RF4B (Room 4B) and RF5 (Room 5) showed 25.8% and 30% improvement, respectively. Finally, it is important to mention that the average improvement by K-span roof cover in this study was 44%, and this value could be higher if the roof cover was treated using another insulation strategy.